CITRUS HYSTRIX DC DARI JAWA TENGAH DAN SUMBA TIMUR KOLEKSI KEBUN RAYA BOGOR - Astuti, Inggit Puji; Ajiningrum, P. S. (Perhimpunan Biologi Indonesia, 2019)
ABSTRACTBoth Citrus macroptera Montrouz. and Citrus micrantha Wester were cited as different species from C. hystrix by several authors. Morphological characters that can be used to differentiate those species are leaf shape and fruit. C. hystrix is cultivated at Bogor Botanic Gardens originated from Central Java Province and East Sumba Island, East Nusa Tenggara Province. In previous study, C. hystrix, both from Central Java and East Nusa Tenggara, did not produce flowers as well fruit yet. The only useful characters for differentiation of the species were leaf morphology and its thorns. Therefore, further study is needed. The research was carried out from January 2013 to December 2018 at Bogor Botanic Gardens and the Anatomy and Cytology Laboratory, Botany Department, Research Center of Biology LIPI. Flower and fruit morphology have been observed on C. hystrix originated from both Central Java and East Nusa Tenggara as well as from other localities which is commonly used. To support this reasearch then leaf and petiole anatomy have been done. The result showed that morphological characters of leaf shape and fruit of C. hystrix where originated from Central Java, differed from C. hystrix originated from East Nusa Tenggara and those are commonly used by local people. However, based on leaf and petiole anatomy observations of all specimens used on this research are quantitavely similar, so that these results are not supported the morphological characters observation. Therefore, it is assumed that both C. hystrix, originated from Central Java and East Nusa Tenggara, as variety of C. hystrix that commonly used by local people.